Anelasticidade em titânio, tântalo e na liga Ti-40Ta - Patricio, Marco Antonio Tito (2014)
The growing demand for increasingly resistant and biocompatible with the human body implantable materials, has led to an increase in demand for new metallic biomaterials. Some materials, such as titanium and its alloys, especially the Ti-6Al-4V, are widely used in the manufacture of orthopedic implants due to their excellent biocompatibility, high corrosion resistance and low density. However, the characteristics of these materials are not considered optimal, mainly because they have a high value of the elastic modulus when compared to the human bone. Include, that in the last decade studies have revealed diseases associated with elements such as Al and V, present in the alloy Ti-6Al-4V. Thus, it have looked for alternatives to the alloys used as biomaterials, still having one common element titanium, but having no toxic elements such as 𝛽 type titanium alloys, formed by non-toxic elements such as Nb, Ta, Zr, Mo and Sn has shown that lower values of modulus, greater fatigue resistance and corrosion resistance, exhibiting excellent biocompatibility. Accordingly, the alloys formed by Ti-Ta become promising candidates as biomaterials, since it has been observed that the content of Ta affects the value of the elastic modulus. For some compositions of this alloy, lower modulus values of this alloys that are currently used in biomedical applications were observed. However, the alloys formed by Ti-Ta still have properties that have been little studied. Thereby, the objectives of this master s project consist in getting the alloy Ti-40Ta and its characterization by means of the technique of mechanical spectroscopy, as of its elements that compose the alloy. The technique of mechanical spectroscopy to be non-destructive, it is widely used for providing the anelastic spectrum (oscillation frequency and internal friction as a function of temperature) is considered sensitive to phase transitions and dynamic processes, which are essential for understanding the structural changes occurring in these materials. This study was determined the dynamic elastic modulus for the pure Ti and Ta elements, and the Ti-40Ta through flexural vibrations. The elastic modulus found for the alloy at room temperature was (71 ± 5) GPa, which is in accordance with results available in the literature. The value of modulus of the alloy is lower when compared to the commercial biomedical alloys and is closer to that of human bone, which makes the alloy Ti-40Ta a potential candidate to be used in biomedical applications.